2011
DOI: 10.1016/j.jcrs.2011.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of distraction on simulated anterior segment surgical performance

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…This differs from the 2010 study by Park [7], where performance in the cognitive task declined significantly when the candidates were dual-tasking -studies with larger sample sizes, or more challenging tasks, would be helpful to investigate this further.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This differs from the 2010 study by Park [7], where performance in the cognitive task declined significantly when the candidates were dual-tasking -studies with larger sample sizes, or more challenging tasks, would be helpful to investigate this further.…”
Section: Discussionmentioning
confidence: 77%
“…With the advent of virtual reality simulators it is now possible to study the effects of different conditions on surgical outcomes without compromising patient safety [7][8][9][10]. Simulators have been used to study how distractions can influence surgical outcomes [11], including during intraocular procedures involving the anterior segment by Park et al [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, possible to do so with the use of an ophthalmic simulator, which we previously used to show other variables that cannot be observed on real patients, such as the effect of distraction, fatigue, and loss of stereopsis on surgical performance. [1][2][3] The aim of this study was to establish the safety of nondominant-hand simulated intraocular surgery.…”
mentioning
confidence: 99%
“…Certain modules on this simulator have been validated, such that performance on the simulator has been shown to reflect performance in the operating theatre (Mahr & Hodge 2008). Waqar et al (2011) and Park et al (2011) have demonstrated this, as a useful tool to investigate parameters relevant to an ophthalmic surgeon such as fatigue and distraction.…”
Section: Introductionmentioning
confidence: 99%